2022
DOI: 10.1039/d1fo03078g
|View full text |Cite
|
Sign up to set email alerts
|

Memory enhancement effect of saponins from Eleutherococcus senticosus leaves and blood–brain barrier-permeated saponins profiling using a pseudotargeted monitoring strategy

Abstract: Dried Eleutherococcus senticosus leaves (ESL), also known as Siberian ginseng tea, are beneficial for human neural disorders. Our previous studies showed that the aqueous extract of ESL enhanced memory in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The results of some studies have shown that TS from E. senticosus leaves can permeate the blood–brain barrier to exert neuroprotective effects 22,23 . The current characterized structures of TS from the ESF extract were similar to the bioactive structures in E. senticosus leaves.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The results of some studies have shown that TS from E. senticosus leaves can permeate the blood–brain barrier to exert neuroprotective effects 22,23 . The current characterized structures of TS from the ESF extract were similar to the bioactive structures in E. senticosus leaves.…”
Section: Resultsmentioning
confidence: 57%
“…20 Our previous studies revealed that TS isolated from E. senticosus leaves can protect neurons from Aβ 25-35 -induced toxicity and permeate the blood-brain barrier to enhance the memory and learning ability of animals. [21][22][23] ESF has also been applied in folk medicine to treat neurological diseases. 1 TS extracted from ESF were recently reported to exert neuroprotective effects by inhibiting neuroinflammation in lipopolysaccharide-treated BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The root is ground into a powder and taken in capsules or as a tincture. A decoction known as Siberian ginseng tea is made from dried leaves [ 84 , 91 ].…”
Section: Specific Nootropic Herb Shrub and Tree Speciesmentioning
confidence: 99%
“…This phenomenon also occurs in the caffeine study, where the low dose (4 mg/kg) of caffeine inhibited the 5‐HT level in SD rats (Lim et al, 2001) while the high dose (30 mg/kg) in Wistar rats made the 5‐HT increased (Khaliq et al, 2012). Furthermore, the dosage differences of ES had been found to perform inconsistent neural protective effects in some studies (Huang et al, 2022). In addition to the 5‐HT, Jin et al also discovered that the content of cAMP‐response element‐binding (CREB) protein in the hippocampus was significantly increased with gavage doses of 1 and 2 g/kg ES in mice.…”
Section: Nds Relevant Pharmacological Effectsmentioning
confidence: 99%